(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study intended to examine the needs of oral care and to provide the basic data required to develop related products through the trend analysis on the relation between the chronic disease and the oral health according to the diabetes treatment. Methods/Statistical analysis: 458,301 research subjects older than 45 years were selected by requesting the raw data of 2015, 2016 and 2017 local community health survey. For the data analysis, the statistical software R program was used, and the significant level was less than 0.05. Findings: In case of having diabetes, it was shown that the hypertension, arthritis, depression etc. were significantly high out of the chronic disease and the subjective health level was also poor (p<0.001). In the oral health, in case of having diabetes, as the subjective oral health level was poor such as subjective periodontal tissue health level was poor and the mastication was inconvenient and the subjective oral health level was poor. Improvements/Applications: For the patient with diabetes, diverse measures for the management of complications of the chronic disease and oral health care should be prepared at national level for the systematic oral health care.